THE PRINCIPLES OF INTERPRETATION OF THE POETIC PRIMARY SOURCE IN BALLADS BY F. SCHUBERT, S. MONIUSZHKO, H. WOLF ON GOETHE’S TEXT «KENNST DU DAS LAND» - GOVORUKHINA, Nataliya (Studia Universitatis Babes-Bolyai Musica, 2022)
We propose to study the ways of embodying the poetic text of Goethe’s poem by three composers (F. Schubert, S. Moniuszko, H. Wolf) by analyzing the patterns of the poetic text structural and functional method (repetition, system of repetitions, update) and its relationship with the musical and poetic method at the level of the general structure and individual techniques (duplication, replacement) with the involvement of the comparative method. The need to reveal the meaning and value of a particular technique led to the use of the semantic method. In comparison with other romantic examples – F. Schubert and H. Wolf, which continuously attract the attention of researchers, the composer’s version of S. Moniuszko is involved. As a result of the analysis, we made a conclusion about the relative constancy in all three selected samples of the implementation of repetition both at the level of the entire text (three stanzas), the structure of the stanza, and at the level of keywords (question “Kennst du…”), at that time, the renewal in the poetic text observed in the second and third stanzas of Goethe’s poem, is embodied in different musical and poetic forms — from leveling changes (S. Moniuszko) to their consistent implementation (H. Wolf). The only exception to this is the “chorus”, in which J. Goethe presents variant appeals of the female protagonist to different addressees — composers interpret them identically (the poetic text is renewed and the musical text remains unchanged), which also acts as a constant element of the interpretation of the poetic original source.